WORKING WITH MULTILEVEL ESP GROUP STUDENTS - Mirzokulova , Xursanoy Ne’matjonovna (Innovative Development in Educational Activities, 2024)
ESP stands for "Working with multilevel ESP group students" and refers to the teaching and learning of English for a specific purpose or field, such as business, medicine, or engineering.